2011
DOI: 10.1073/pnas.1112151108
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 9- cis -epoxycarotenoid dioxygenase in Arabidopsis thaliana seeds enhances seed dormancy

Abstract: Full understanding of mechanisms that control seed dormancy and germination remains elusive. Whereas it has been proposed that translational control plays a predominant role in germination, other studies suggest the importance of specific gene expression patterns in imbibed seeds. Transgenic plants were developed to permit conditional expression of a gene encoding 9-cis-epoxycarotenoid dioxygenase 6 (NCED6), a rate-limiting enzyme in abscisic acid (ABA) biosynthesis, using the ecdysone receptor-based plant gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 49 publications
3
103
0
1
Order By: Relevance
“…10; Supplemental Table S2). Previous studies indicated that NCED6 is highly expressed in the testa and endosperm, and its overexpression results in increased ABA levels in seeds and enhanced seed dormancy (Lefebvre et al, 2006;Martínez-Andújar et al, 2011). The up-regulation of NCED6 expression in cer9 mutant seeds thus may contribute to the higher ABA level and increased seed dormancy of the mutants.…”
Section: Discussionmentioning
confidence: 95%
“…10; Supplemental Table S2). Previous studies indicated that NCED6 is highly expressed in the testa and endosperm, and its overexpression results in increased ABA levels in seeds and enhanced seed dormancy (Lefebvre et al, 2006;Martínez-Andújar et al, 2011). The up-regulation of NCED6 expression in cer9 mutant seeds thus may contribute to the higher ABA level and increased seed dormancy of the mutants.…”
Section: Discussionmentioning
confidence: 95%
“…Specific induction of NCED6 during Arabidopsis seed development is sufficient to enhance seed dormancy (Martínez-Andújar et al, 2011). In mature lettuce seeds, NCED4 mRNA is present in the embryo, but not in the endosperm ; information on NCED4 expression during lettuce seed development has not been reported.…”
Section: Expression Of Nced Family Members and Other Genes During Letmentioning
confidence: 99%
“…NCED3 together with NCED5 are important regulators of ABA levels during water stress in Arabidopsis, and their transcripts are induced by drought (Tan et al, 2003;Ruggiero et al, 2004;Frey et al, 2012). Arabidopsis NCED5, NCED6, and NCED9 play important roles in ABA synthesis in the embryo and endosperm during dormancy induction (Lefebvre et al, 2006;Seo et al, 2006;Martínez-Andújar et al, 2011;Frey et al, 2012). NCED6 is regulated by light and its mutation promoted seed germination in the dark, whereas NCED9 and NCED5 are induced by high temperature in the imbibed seeds and their mutation resulted in loss of thermoinhibition Toh et al, 2008).…”
Section: Nced4 Shows Distinct Expression From Other Nced Genes In Letmentioning
confidence: 99%
“…Altered expression of genes regulating ABA levels or sensitivity leads to changed seed dormancy levels (Rodríguez-Gacio et al, 2009). Induction of NCED6 during imbibition increases ABA levels and is sufficient to prevent seed germination (Martínez-Andújar et al, 2011). The ABA 89-hydroxylase mutants cyp707a2 and cyp707a1 and the double mutant cyp707a2 cyp707a1 accumulate ABA in dry and imbibed seeds and exhibit enhanced seed dormancy (Saito et al, 2004;Okamoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%